Trajetória e pensamento intelectual de professoras da PUC-Rio. Representantes de uma geração de Teólogas Feministas - Furlin, Neiva (Revista eclesiástica brasileira, 2014)
This article is part of the set of studies of the sociology of knowledge. It analyses aspects of the performance of three theologians and teachers at Pontifical Catholic University of Rio de Janeiro (PUC-Rio), among the pioneer women in Brazil who produced a theology according to the Feminist perspective and the approach of Gender Studies. It seeks to verify elements of these women’s curriculum and performance which make them representatives of their generationof feminist theologians. The empirical data of this study were collected through bibliographical research and elaborated interviews during the year of 2009, and are analyzed in the light of the generation problems theory of Karl Mannheim (sociologist).